Polyphosphate in Lactobacillus and Its Link to Stress Tolerance and Probiotic Properties - Alcántara, Cristina; Coll-Marqués, José M.; Jadán-Piedra, Carlos; Vélez, Dinoraz; Devesa, Vicenta; Zúñiga, Manuel; Monedero, Vicente (Frontiers in Microbiology, 2018)
The synthesis of the inorganic polymer polyphosphate (poly-P) in bacteria has been linked to stress survival and to the capacity of some strains to sequester heavy metals. In addition, synthesis of poly-P by certain strains of probiotic lactobacilli has been evidenced as a probiotic mechanism due to the homeostatic properties of this compound at the intestinal epithelium. We analyzed the link between poly-P synthesis, stress response and mercury toxicity/accumulation by comparing wild-type strains of Lactobacillus and their corresponding mutants devoid of poly-P synthesis capacity (defective in the poly-P kinase, ppk, gene). Results showed that resistance to salt (NaCl) and acidic (pH 4) stresses upon ppk mutation was affected in Lactobacillus casei, while no effect was observed in two different Lactobacillus plantarum strains. Inorganic [Hg(II)] and organic (CH3Hg) mercury toxicity was generally increased upon ppk mutation, but no influence was seen on the capacity to retain both mercurial forms by the bacteria. Notwithstanding, the culture supernatants of ppk-defective L. plantarum strains possessed a diminished capacity to induce HSP27 expression, a marker for cell protection, in cultured Caco-2 cells compared to wild-type strains. In summary, our results illustrate that the role of poly-P in stress tolerance can vary between strains and they reinforce the idea of probiotic-derived poly-P as a molecule that modulates host-signaling pathways. They also question the relevance of this polymer to the capacity to retain mercury of probiotics.